Checkpoint Blockade Toxicity and Immune Homeostasis in the Gastrointestinal Tract - Dougan, Michael (Frontiers in Immunology, 2017)
Monoclonal antibodies targeting the regulatory immune “checkpoint” receptors CTLA-4, PD-1 and PD-L1 are now standard therapy for diverse malignancies including melanoma, lung cancer, and renal cell carcinoma. Although effective in many patients, and able to induce cures in some, targeting these regulatory pathways has led to a new class of immune related adverse events (irAEs). In many respects, these immune toxicities resemble idiopathic autoimmune diseases such as inflammatory bowel disease, autoimmune hepatitis, rheumatoid arthritis, and vitiligo. Understanding the pathogenesis of these immune toxicities will have implications not only for care of patients receiving checkpoint blockade, but may also provide critical insights into autoimmune disease. The GI mucosa is arguably the most complex barrier in the body, host to a diverse commensal microflora and constantly challenged by ingested foreign proteins both of which must be tolerated. At the same time, the GI mucosa must defend against pathogenic microorganisms while maintaining sufficient permeability to absorb nutrients. For these reasons, regulatory cells and receptors are likely to play a central role in maintaining the gut barrier, and gastrointestinal toxicities such as colitis and hepatitis are indeed among the most common side effects of CTLA-4 blockade and to a lesser extent blockade of PD-1 and PD-L1. High dose corticosteroids are typically effective for management of both checkpoint colitis and hepatitis, although a fraction of patients will require additional immune suppression such as infliximab. Prompt recognition and treatment of these toxicities is essential to prevent more serious complications.